Literature Review on Unnatural Narrative Theory - Wu, Sufen (Journal of Social Science Studies, 2021)
Unnatural narrative becomes a popular theory in literary criticism. In 2016, No. 4 issue of Style is a special issue on Brian Richardson’s Target Essay “Unnatural Narrative Theory”. Narratologists such as Marie-Laure Ryan, Shen Dan, and James Phelan have responded actively to this new paradigm in narrative theory. In spite of its popularity, unnatural narrative remains controversial because of its diversified definitions, the hard-to-identified manifestations of unnaturalness, and its various interpretive strategies. Accordingly, this paper tries to comb the existing literature and provide a systematic review on the definitions, the manifestations, and the interpretive strategies of unnatural narrative theory.